ANALISIS PENGARUH ELECTRONIC MONEY TERHADAP JUMLAH UANG BEREDAR DAN VELOCITY OF MONEY DI INDONESIA - Agustin Kristi Antri Rahayu,; Iffatin Nur, (Juremi: Jurnal Riset Ekonomi, 2022)
The purpose of this study is to determine whether electronic money has an effect on the money supply and velocity of money in Indonesia. Technological developments that are increasingly developing affect payment systems that used to use cash to become e-money. E-money is starting to develop and is in demand by the public because it is considered more efficient and effective. The increasing use of electronic money (e-money) by the public has an impact on the money supply (M1) in Indonesia and the velocity of money. This study uses a quantitative approach with the type of associative research. This study uses secondary data sources. The sample in this study is the value of the volume of electronic money, the value of the money supply and the value of the velocity of money in Indonesia in 2012-2021. This study uses secondary data sources. The data analysis method used in this research is simple linear regression analysis. The result of this research is that e-money has a significant effect on the money supply. Electronic money contains float funds that are highly liquid which can be used to make legal payment transactions. So when the value of float funds increases, the amount of money in circulation in the community also increases. Electronic money has a significant effect on the velocity of money, when many people use e-money, fewer people use cash to make transactions.